Exploring the Neandertal legacy of pancreatic ductal adenocarcinoma risk in Eurasians - Piccardi, Margherita; Gentiluomo, Manuel; Bertoncini, Stefania; Pezzilli, Raffaele; Erőss, Bálint; Bunduc, Stefania; Uzunoglu, Faik G.; Talar-Wojnarowska, Renata; Vanagas, Tomas; Sperti, Cosimo; Oliverius, Martin; Aoki, Mateus Nóbrega; et al. (Biological research, 2023)
BACKGROUND: The genomes of present-day non-Africans are composed of 1-3% of Neandertal-derived DNA as a consequence of admixture events between Neandertals and anatomically modern humans about 50-60 thousand years ago. Neandertal-introgressed single nucleotide polymorphisms (aSNPs) have been associated with modern human disease-related traits, which are risk factors for pancreatic ductal adenocarcinoma (PDAC), such as obesity, type 2 diabetes, and inflammation. In this study, we aimed at investigating the role of aSNPs in PDAC in three Eurasian populations. RESULTS: The high-coverage Vindija Neandertal genome was used to select aSNPs in non-African populations from 1000 Genomes project phase 3 data. Then, the association between aSNPs and PDAC risk was tested independently in Europeans and East Asians, using existing GWAS data on more than 200 000 individuals. We did not find any significant associations between aSNPs and PDAC in samples of European descent, whereas, in East Asians, we observed that the Chr10p12.1-rs117585753-T allele (MAF = 10%) increased the risk to develop PDAC (OR = 1.35, 95%CI 1.19-1.54, P = 3.59 × 10-6), with a P-value close to a threshold that takes into account multiple testing. CONCLUSIONS: Our results show only a minimal contribution of Neandertal SNPs to PDAC risk.
Gesehen am 17.06.2024